KEMAMPUAN DAN MOTIVASI DALAM MENINGKATKAN KINERJA PADA PEGAWAI DI KELURAHAN SEI PUTIH TIMUR 1 KECAMATAN MEDAN PETISAH MEDAN - Hanny Siagian; Rayu Sri Wahyuni (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2021)
Urban Village has the main task of carrying out government, development and community affairs (article 4 paragraph 1 of the Republic of Indonesia Government Regulation No. 73 of 2005 concerning Urban Village). The community's demands for good public services cannot be separated from the existence of the urban village which is very close to the local residents. The complaints that arise from local residents indicate that the service is still not satisfactory in terms of speed of completion of work in administrative matters, this is related to the ability and motivation of Human Resources (employees). Extension activities provide education in the form of lectures and discussions as well as evaluation of knowledge before and after counseling. The results of the extension activities showed that there was an increase in additional knowledge of 25.11% after the extension was carried out. It is hoped that this counseling activity can be sustainable in an effort to improve work skills and motivation to improve employee performance in providing services to the community in accordance with the duties and functions of the urban village.